The impact of the IPA cross-border co-operation Hungary - Croatia 2007 - 2013 programme - infrastructure, tourism and human capital - Ravlić, Sanela (Array, 2020)
The main purpose of the paper is to move towards quantification and clear distinction of invested IPA funds in the CBC area of Hungary and Croatia 2007. - 2013. Objective of the paper is to provide an insight into the real impact of allocated financial resources to the extent that was not examined so far at the level of institutions (lead beneficiary and project partners) and target group members. The main research questions is what is the impact that implemented projects in IPA CBC HU – CRO had in terms of different types of institutions, types of activities (educational or infrastructure), beneficiaries in local communities and regional development? The research was conducted in April/May 2018. The questionnaire consisted of 41 variables. Interview was the corrective method. Data analysis was conducted using SPSS v23. Total of 102 respondents participated, representing 358 institutions that implemented projects in the cross-border area. Data were first analysed using descriptive statistics, then compared by using t-test and ANOVA Chi-square test was performed to determine the likelihood of correlation between variables. Paper shows obtained results on personal, organisational and regional level. The outcome confirms the difference between human capital in institutions that implement projects and high dependence of EU funds in entire region. Beneficiaries are more aware of impact that lifelong learning activities can have on their labour market competitiveness. Investment in sustainable environment, tourism, development of economic cooperation, infrastructure and common human capacities will have a significant impact in the region.